2022
DOI: 10.3390/math10040613
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and the Matthew Effect in the European Union Based on the DESI Index

Abstract: The European Commission (EC) has monitored Member States' digital progress through the Digital Economy and Society Index (DESI) since 2014. The DESI index currently ranks the EU Member States and monitors their progress based on four core and 33 individual indicators. We sought to determine whether convergence between the Member States could be detected using the DESI’s annual databases. By examining the variation in the indices, we propose the existence of a so-called “Matthew effect”, i.e., the “rich get ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…EU countries have been ranked according to the factor scores. As has been previously mentioned, this study confirmed some of the previous findings of other authors, e.g., Kinnunen et al [13], Borowiecki et al [14], Orviska and Hunady [49], Cheba et al [50], Kovács et al [54], etc. This study brings some new empirical insight into the digital economy problem and businesses' readiness for digital transformation in the EU.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…EU countries have been ranked according to the factor scores. As has been previously mentioned, this study confirmed some of the previous findings of other authors, e.g., Kinnunen et al [13], Borowiecki et al [14], Orviska and Hunady [49], Cheba et al [50], Kovács et al [54], etc. This study brings some new empirical insight into the digital economy problem and businesses' readiness for digital transformation in the EU.…”
Section: Discussionsupporting
confidence: 93%
“…However, they decided to use only four main clusters instead of three and seven sub-clusters in this paper [14]. In addition, Kovács et al [54] also used DESI in their analysis and revealed Denmark, Netherlands, Finland, and Sweden to have the highest internet services digital readiness. Nevertheless, the approach used in this paper is also unique due to the selection of variables.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Marcysiak and Pleskacz (2021) analysed the degree of digitisation (DESI) in the Polish economy in comparison with the EU average, with particular emphasis on SMEs. Kovács et al (2022) used correlation analysis and principal component analysis to analyse the digital economy and society index. Leogrande et al (2022a) analysed the determinants of the "Broadband Price Index" in 28 European countries between 2014 and 2021 and used data of DESI.…”
Section: Desimentioning
confidence: 99%
“…Our results cannot be compared with existing research because, as stated in Literature Review (see Section 1), we are not aware that there exists research that has focused on cluster analysis. The research focuses mainly on comparing only a few countries (e.g., Moroz, 2017;Stoica & Bogoslov, 2017;Burlacioiu et al, 2018;Kontolaimou & Skintzi, 2018;Grinberga-Zalite & Hernik, 2019;Karnitis et al, 2019;Nagy, 2019), or other methods were used (e.g., Gerasenko & Levkovich, 2019;Kovács et al, 2022;Kutnjak et al, 2020;Leogrande et al, 2022a). Therefore, this paper filled research.…”
Section: Cluster Analysismentioning
confidence: 99%
“…An overview of research focused on digital transformation based on the systematization of literary sources was conducted by Kraus et al (2021). Kovács et al (2022) investigate the convergence of countries based on the DESI indicator. They use the beta convergence and the sigma convergence methods.…”
Section: Literature Reviewmentioning
confidence: 99%